A Multi-group Analysis of Gender Difference in Consumer Buying Intention of Agricultural Products via Live Streaming - Zhu, Bing; Xu, Ping; Wang, Ke (Research on World Agricultural Economy, 2023)
This study tries to understand the determinants of Chinese consumers' purchase behavior and reveal the role of gender in shaping consumers’ buying decisions for agricultural products from live-streaming platforms. For this purpose, an online survey was carried out to collect data in Southern China. Partial least squares structural equation modeling (PLS-SEM) was employed for path analysis and multi-group analysis. The results confirm the substantial influences of consumer attitude, subjective norms and perceived behavioral control on consumer buying intention. Next, gender difference only exists concerning the effect of perceived behavioral control on consumer intention. However, the gap between male and female consumers on this point is small. Furthermore, as each factor affects consumers' purchase intention differently, corresponding implications are provided. ER